Nano-governance, nano-regulation and nanocitizenship? An analysis of normative scenarios in Brazil and Argentina - Berger, Mauricio (2017)
Fil: Berger, Mauricio. Universidad Nacional de Córdoba. Facultad de Ciencias Sociales; Argentina.